Returning to reality : Thomas Merton's wisdom for a technological age - Thompson, Phillip M., 1959- (Cambridge : Lutterworth Press, 2013)
We are becoming a nation of superficial and distracted consumers of instant messages and images, a state of being which does not aid engagement in religious and other deep commitments that require a sustained level of reflection and contemplation. In his thought-provoking work, Phillip M. Thompson analyses the shadow elements of technology - nuclear armaments, the bio-engineering of humans, and the distancing of humanity from the natural world - through the fascinating insights of the spiritual writer and monk Thomas Merton (1915-1968). Merton's work offers an important critique and healing re.
A contemplative critique -- Avoiding the nuclear apocalypse -- Reforming the information age -- Choosing to be human or transhuman -- Some balm for Gilead -- Conclusion: From the watchtower.
Includes bibliographical references.
Print version record.
OCLC control number change - Master record variable field(s) change: 072, 650
Keywords: Merton, Thomas, -- 1915-1968.; Technology -- Religious aspects -- History -- 20th century; Technology -- Philosophy; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; RELIGION -- Christian Theology -- General; Electronic books